Level of stroke knowledge and stroke risk factors among home-based first ever stroke patients in Kota Bharu - Razak, Rosmawani Ab (Universiti Sains Malaysia, 2016)
Stroke is common diseases that related to the people disability. It also most common cause of death worldwide after coronary heart diseases. At the same times, Malaysia National Burden of Diseases reported stroke is two leading causes of death in Malaysia which is estimated about 12.1% in female and 8.9% in male. The main causes of the increasing of the mortality and morbidity of stroke due to lack of knowledge regarding stroke among patients. Therefore, this study are conducted to identify the level of stroke knowledge and what common risk factors among first-ever stroke patients who are already discharge from Hospital LTSM. The purposes of the study are also to identify the associations between socio-demographic data with level of stroke knowledge and association between stroke risk factors and stroke knowledge. This cross-sectional study was performed to 50 respondents which are half from exactly respondents that required. The information regarding the respondents is getting from Hospital USM record department. The respondents are those who first-ever stroke, above eighteen years old, live in area in Kota Bharu, and does not have any neurological problem. The questionnaires provided are self-administered questionnaires which consist two sections. Section A is socio-demographic data, Section B is Stroke Knowledge Test (SKT) by Sullivan. This study resulted with 70% of the respondents are poor knowledge and only 30% are good knowledge. The socio-demographic data (level of education, financial and type of works before stroke) are show an independent significant with the level of stroke knowledge with (p= 0.010, 0.044, 0.014) p<0.05. However, some of the socio-demographic data are not significant associated with the level of knowledge such as age, gender, and risk factors of stroke (P>0.05). Therefore, the findings are suggested the implement of educational program regarding stroke knowledge are important in increased the level of stroke knowledge among patients before discharge to prevent the recurrence of stroke that would be more severe.